1978
DOI: 10.1007/bf01563699
|View full text |Cite
|
Sign up to set email alerts
|

Follow‐up results after resection of thoracic esophageal carcinoma

Abstract: During the past 14.5 years, we have treated 430 patients with carcinoma of the thoracic esophagus. The resection rate was 72% and the overall operative mortality rate was 16%. During the past 5 years, the operative mortality rate has been markedly reduced to 4.5%. The low operative mortality rate in recent years is the result of selection of the operative procedure according to the criteria that we have established for one-stage radical rese~ion. The overall 5year survival rate was 16.5%. Prophylactic postoper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0
1

Year Published

1980
1980
1999
1999

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(31 citation statements)
references
References 9 publications
(17 reference statements)
0
30
0
1
Order By: Relevance
“…The difference of survival rates as related to the waiting period became clear after the follow-up of more than four years. The prognostic difference of subclinical tumors seems to be uncovered several years after treatment, esophageal carcinoma; surgery; postoperative irradiation; waiting period Postoperative irradiation for esophageal carcinoma has improved the prognosis (Kasai et al 1978;Nishihira et al 1984). In general, postoperative irradiation should be started as soon as possible after surgery, because a delay of the irradiation may result in regrowth of the residual tumor cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The difference of survival rates as related to the waiting period became clear after the follow-up of more than four years. The prognostic difference of subclinical tumors seems to be uncovered several years after treatment, esophageal carcinoma; surgery; postoperative irradiation; waiting period Postoperative irradiation for esophageal carcinoma has improved the prognosis (Kasai et al 1978;Nishihira et al 1984). In general, postoperative irradiation should be started as soon as possible after surgery, because a delay of the irradiation may result in regrowth of the residual tumor cells.…”
mentioning
confidence: 99%
“…Postoperative irradiation for esophageal carcinoma has improved the prognosis (Kasai et al 1978;Nishihira et al 1984). In general, postoperative irradiation should be started as soon as possible after surgery, because a delay of the irradiation may result in regrowth of the residual tumor cells.…”
mentioning
confidence: 99%
“…As Kasai reported previously, however, postoperative radiotherapy against esophageal cancer was quite effective for patients with negative nodes, but not for patients with positive nodes (Kasai et al 1978). Thereafter, 78 patients were treated with postoperative radiotherapy.…”
mentioning
confidence: 66%
“…Two Japanese studies favor the use of postoperative RT, one using historical controls (21) and one randomized trial (22). In a French randomized trial, however, comparing surgery with surgery followed by RT including 221 patients it was shown that postoperative RT (45-55 Gy, 1.8 Gy/fraction) did not affect survival after curative esophageal resection (23).…”
Section: Local and Loco-regional Treatmentmentioning
confidence: 99%